2023
DOI: 10.1039/d2rp00175f
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of students’ diagrams of water molecules in snowflakes to reveal their conceptual understanding of hydrogen bonds

Abstract: Recent studies have reported a growing trend of using student-generated diagrams for assessment in science teaching and research. However, many educators tend to use diagrams to explore students’ perceptions of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 47 publications
(94 reference statements)
0
8
0
Order By: Relevance
“…There are many studies on diagrams in the field of education (Akgün & Özkar Bulut, 2017;Diezmann, 2005;Diezmann, 2006;Diezmann & English, 2001;Doğmaz, 2016;Gobert & Clement, 1999;Liu, Won & Treagust, 2014;Kidman, 2002;McLure vd., 2022;Pantziara vd., 2009;Tippett, 2016). Many of these studies are related to diagram reading skills (Akgün & Bulut Özkar, 2017;Diezmann, 2005;Diezmann & English, 2001;Doğmaz, 2016;Kidman, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many studies on diagrams in the field of education (Akgün & Özkar Bulut, 2017;Diezmann, 2005;Diezmann, 2006;Diezmann & English, 2001;Doğmaz, 2016;Gobert & Clement, 1999;Liu, Won & Treagust, 2014;Kidman, 2002;McLure vd., 2022;Pantziara vd., 2009;Tippett, 2016). Many of these studies are related to diagram reading skills (Akgün & Bulut Özkar, 2017;Diezmann, 2005;Diezmann & English, 2001;Doğmaz, 2016;Kidman, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been observed that the use of diagrams in education has increased in concept learning and the evaluation of conceptual knowledge (Matovu, Won, Treagust, Mocerino, Ungu, Tsai, & Tasker, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The descriptors of the conceptual categories, together with exemplar verbal explanations are summarised in Table 1. The detailed analysis of the student-generated diagrams has been discussed in a separate manuscript (Matovu et al, 2022b).…”
Section: Discussionmentioning
confidence: 99%
“…In chemistry education, several studies have used studentgenerated diagrams to assess the level of students' conceptual understanding of key chemistry concepts. The concepts investigated included the particle theory of matter (e.g., Andrade et al, 2021;McLure et al, 2021a), atomic structure (e.g., Derman et al, 2019), and intermolecular forces (e.g., Cooper et al, 2015;Noyes and Cooper, 2019;Matovu et al, 2022b). In IVR research, however, few studies have used drawing tasks to assess students' science conceptual understanding.…”
Section: Introductionmentioning
confidence: 99%
“…Still, this trend contributes to the decline in chemistry studies in higher education. Chemistry is often perceived as a challenging field that requires abstract thinking (Taber, 2018;Gulacar et al, 2020;Avargil et al, 2021;Matovu et al, 2022) and a substantial investment of time, patience, and perseverance (Salta et al, 2012). These perceptions contribute to the notion that chemistry is not a popular career choice, with a declining trend in recent years.…”
Section: Introductionmentioning
confidence: 99%